Wilhelm J.G. Möhlig and Jekura U. Kavari 2008. Reference Grammar of Herero (Otjiherero). Bantu Language of Namibia. - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
First and foremost one should note that the book under review needs to be treated as the leading book for the description of Bantu languages and that other authors, for Bantu languages at least, will get enlightened by this book. The large part of the book contains the description of the grammar of Herero (R30, Guthrie 1967-71), a Bantu Language spoken mainly in Namibia, respectively Angola and Botswana; but there are two chapters, one containing Otjiherero texts and the other containing the glossary of Otjiherero-English-Otjiherero. The cry from linguists and Bantuists for the lack of detailed and well described data for specific Bantu languages has been heard over a century now, and we have been witnessing Bantuists for some decades embarking and continuing to board on a train of analysing and describing Bantu languages to cater for this need. But of recent (within this decade or so), several reference grammar books have been produced, although the exercise cannot claim to have managed half the demands as it needs resources, both human and material, to cater for the grammars of about 500 Bantu languages (Maho 2003, Nurse 2008) scattered over a vast area south of the Sahara desert. The book under review at least reduces the number of Bantu languages to be prescribed in the contemporary outlook. Also, one notices that the grammar books differ significantly with respect to the organization of the materials, content, and tackling of problematic issues like tone, among others. The Reference Grammar of Herero (Otjiherero) has appeared and will become a standard that others should mirror.